2015
DOI: 10.3390/ijms161025264
|View full text |Cite
|
Sign up to set email alerts
|

Increased Uptake of Chelated Copper Ions by Lolium perenne Attributed to Amplified Membrane and Endodermal Damage

Abstract: The contributions of mechanisms by which chelators influence metal translocation to plant shoot tissues are analyzed using a combination of numerical modelling and physical experiments. The model distinguishes between apoplastic and symplastic pathways of water and solute movement. It also includes the barrier effects of the endodermis and plasma membrane. Simulations are used to assess transport pathways for free and chelated metals, identifying mechanisms involved in chelate-enhanced phytoextraction. Hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 96 publications
0
1
0
Order By: Relevance
“…Furthermore, results show that although there are no statistical differences between covered cropped strategies (MC vs PC) for the leaching of zoxamide, monoculture covered columns resulted in a greater reduction of copper leaching than those observed in polyculture covered columns. This is in agreement with the fact that ray grass (Lolium perenne) is a metalaccumulating plant (Healy et al, 2016;Johnson & Singhal, 2015), but also due to the fact that MC columns had greater root biomass than PC columns (22 vs. 11 g in dry weight).…”
Section: Effect Of Fungicide Application Before Rain Event On Ppp Lea...supporting
confidence: 86%
“…Furthermore, results show that although there are no statistical differences between covered cropped strategies (MC vs PC) for the leaching of zoxamide, monoculture covered columns resulted in a greater reduction of copper leaching than those observed in polyculture covered columns. This is in agreement with the fact that ray grass (Lolium perenne) is a metalaccumulating plant (Healy et al, 2016;Johnson & Singhal, 2015), but also due to the fact that MC columns had greater root biomass than PC columns (22 vs. 11 g in dry weight).…”
Section: Effect Of Fungicide Application Before Rain Event On Ppp Lea...supporting
confidence: 86%
“…Plants may exude organic acids and protons making ionic species present in media biologically available for biosurfactants and chelators [96 -100]. These ionic species bind with chelators and then pass through cellular membranes more easily [101,102] Duckweeds are well recognized for their capability to eliminate the metals from the contaminated environment [41,108,109]. Active transport of heavy metals in freefloating aquatic plants occur through roots from where metals are transferred to other plant organs.…”
Section: Mechanism Of Duckweed Phytoremediationmentioning
confidence: 99%
“…From the results of this experiment it can be seen that most of the Cu 2+ is accumulated in the roots for both treatments with/without DTPA. In the experiment carried out by Johnson and Singhal, (2015) it was reported that "When membrane permeability is low, endodermal damage increases shoot Cu 2+ accumulation due to higher apoplastic bypass flow." Whereas, in this study decrease in shoot Cu 2+ accumulation might be due to low apoplastic bypass flow and that the endodermal might be fairly intact in Smooth Amaranth (Amaranthus hybridus L.) seedlings.…”
Section: Amaranthus Hybridusseedlingsmentioning
confidence: 99%
“…Plants use different mechanisms in terms of metal uptake by their roots based on plant species. These mechanisms can be due to absorption, redox potential, organic matter, pH, redox reactions, exchange capacity, temperature http://dx.doi.org/10.4314/bajopas.v12i1.62S Special Conference Edition, November, 2019 Some plants take up metal complexes in the roots via the inside of the plasma membrane in which water and low molecular weight solutes freely diffused known as symplastic pathway (Johnson and Singhal, 2015). The metal uptake via the roots is related to the free ion concentration in solution around the roots.…”
Section: Introductionmentioning
confidence: 99%